GUIDELINES ON THE DIAGNOSIS AND MANAGEMENT OF ACUTE PULMONARY EMBOLISM - Adam Torbicki; Arnaud Perrier; Stavros Konstantinides; Giancarlo Agnelli; Nazzareno Galie; Piotr Pruszczyk; Frank Bengel; Adrian J.B. Brady; Daniel Ferreira; Uwe Janssens; Walter Klepetko; Eckhard Mayer; et al. (Столичная издательская компания, 2016)
Guidelines on the diagnosis and management of acute pulmonary embolism.